Konsep Makrifah Menurut Al-Ghazali (Sebuah Telaah Epistemologis) - Salamah Eka Susanti (HUMANISTIKA : Jurnal Keislaman, 2016)
Lately visible symptoms in the West kematerian bored with life and seek to live spirituality in the East; No one goes to spirituality in Buddhism, there is a spirituality to the Hindu religion and spirituality tak sedikit have also adopted the Islamic religion. In the face of materialism that is sweeping the world today, it needs to be revived spiritualism. Here Sufism with noble teachings of spirituality and morality can play an important role. In the world of Sufism, known by the term makrifah. Epistemologically, makrifah is a science in which there is no doubt whatsoever, he not only protected from all doubt, but also free from any errors and mistakes. This is the “knowledge” that is true, the true reality, atau kebenaran intrinsic built based on perfect belief (Haqq al-Yaqin). Makrifah menurut al-Ghazali ialah “ knowing the secret and rules that consist of the entities”. Makrifah places in the idea of Sufism al-Ghazali not just limited to the recognition of God, but also include the introduction of all His statutes for all creatures. Makrifah, as knowledge essential and reassuring, did not come easily but through struggle (alMujahadah) and exercise (al-Riyadah) heavy, demanding patience and it took a long time to pass through several stations (al-maqamat) and grace God is the impact of the station (al-Maqam) that has beenachieved. This is the path that must be taken by every person who wants to achieve makrifah. According Al-Ghazali, makrifah can not pass the sensory experience and can not be achieved through understanding but through nur of God as Sufi experience. From here revealed all reality that can not be captured by the senses and can not be reached by reason (ratio). To obtain ma’rifah it is a process that is continuous. The more a Sufi obtain ma’rifah of God, the more he knows about the secret of God and he was getting close to God. However, obtaining a perfect ma’rifah of God is not possible for humans is limited (finite), while Godis (infinitife). As for the goal of a Sufi is to meet with God. This is the pleasure that may never be known by anyone other than Allah SWT. If it has been reached, delete all the hardship and the whole desire for heart drowning in pleasure to meet with him. Had thrown into hell, he would not feel the pain of the punishment of hell because she had drowned in that enjoyment. And if offered to him the pleasures of heaven, he will notcare about him because he has reached the highest pleasure and perfect, which no longer higher enjoyment thereof. Al-Ghazali said that it isso difficult to reveal the nature of reality makrifah; ordinary language is not enough to be able to express it appropriately and it is difficult towrite. Even if a Sufi forced to reveal it, she just express it symbolically.